Tracing Controversies in Hacker Networks: Ethical Considerations for Research on Communal Publics - Richterich, Annika (AoIR Selected Papers of Internet Research, 2017)
This paper reflects on the ethical implications of research tracing controversies in digital, communal publics. It addresses two interrelated questions: How private or public are communication platforms commonly used by digitally networked communities? And how should Internet researchers assess, define and treat online environments which are technically public, but suggest varying privacy expectations on the part of involved users? These questions are relevant to a wide range of Internet research; privacy expectations have been discussed with regards to the ethics of using Twitter, Facebook, as well as other social media data. In this paper, I focus on ethical implications of communal debates on controversial subjects. Specifically, I examine how gender- and diversity-related tensions and incidents have been discussed in hacker communities. Within hacker cultures, issues related to gender and diversity have been subject of controversial discussions: This is on the one hand linked to the emergence of feminist hackerspaces and ‘geek feminism’. On the other hand, these debates arose due to grave concerns about harassment and sexism in hacker communities. I argue that the content reflecting such controversies commonly travels across various platforms which imply different degrees of privacy expectations and therefore require distinct ethical considerations. I particularly highlight the relevance of three factors for ethical decision-making when analysing controversies: the vulnerability and public/private status of affected individuals; the privacy expectations suggested by traversed platforms and users’ interactions; and the moral concerns which are at stake in the respective debate.